Effects of hypnotic bromovalerylurea on microglial BV2 cells - Shun Kawasaki (Journal of Pharmacological Sciences, 2017)
An old sedative and hypnotic bromovalerylurea (BU) has anti-inflammatory effects. BU suppressed nitric oxide (NO) release and proinflammatory cytokine expression by lipopolysaccharide (LPS)-treated BV2 cells, a murine microglial cell line. However, BU did not inhibit LPS-induced nuclear translocation of nuclear factor-κB and subsequent transcription. BU suppressed LPS-induced phosphorylation of signal transducer and activator of transcription 1 (STAT1) and expression of interferon regulatory factor 1 (IRF1). The Janus kinase 1 (JAK1) inhibitor filgotinib suppressed the NO release much more weakly than that of BU, although filgotinib almost completely prevented LPS-induced STAT1 phosphorylation. Knockdown of JAK1, STAT1, or IRF1 did not affect the suppressive effects of BU on LPS-induced NO release by BV2 cells. A combination of BU and filgotinib synergistically suppressed the NO release. The mitochondrial complex I inhibitor rotenone, which did not prevent STAT1 phosphorylation or IRF1 expression, suppressed proinflammatory mediator expression less significantly than BU. BU and rotenone reduced intracellular ATP (iATP) levels to a similar extent. A combination of rotenone and filgotinib suppressed NO release by LPS-treated BV2 cells as strongly as BU. These results suggest that anti-inflammatory actions of BU may be attributable to the synergism of inhibition of JAK1/STAT1-dependent pathways and reduction in iATP level.